Achieving sustainable e-government in Pacific Island States - Aqorau, Transform 1964-; Chan Mow, Ioana; Cook, Len; Gisa, Fuatai Purcell; Logan, Sarah; Cullen, Rowena; Hassall, Graham (Cham, Switzerland : Springer, 2018)
This book analyzes the common set of obstacles to the development and integration of government Information and Communication Technology (ICT) projects and effective e-government initiatives in developing countries. It draws on the expertise and experience of more developed states in the Pacific, notably Australia and New Zealand, both highly rated in global rankings for e-government and active in a variety of e-government development projects across the region. There has been a general failure to identify priorities and align projects with local needs in ICT/e-government projects. Small Island Developing States (or SIDS) present a unique problem in terms of e-government. Not only do they suffer from a common set of barriers to ICT development such as their remoteness, geographical dispersion, moist tropical climates, largely rural populations, and lack of ICT capacity and infrastructure, but are also dependent on external agencies for investment, and must negotiate with powerful donors who have conflicting agendas. E-government is widely regarded as 'transformational', increasing efficiency, productivity, accountability, economic growth, and citizen involvement. But while the governments of SIDS are committed to harnessing ICTs for effective government and economic development, they face major challenges in establishing successful e-government initiatives, due to the problems outlined above, coupled with a lack of HR capacities and appropriate strategies and policies. Drawing on the experience of the states mentioned above, as well as regional quasi-governmental bodies, nongovernmental organizations (NGOs), aid agencies, and the private sector, the book will be of interest to researchers and students in the fields of e-government, public administration, political science, communication, information science, and social media.
La función de los autores fue determinada por el catalogador
Keywords: OCEANÍA -- POLÍTICA Y GOBIERNO; administracion pu; REDES DE COMPUTADORAS -- OCEANÍA